Studi Feminisme Terhadap Kegelisahan Usia Ideal Perkawinan Pada Perempuan Bekerja - Rahmah Husna Yana; Nurkhalis Nurkhalis; Irma Juraida; Putri Maulina (Jurnal Community, 2021)
Abstract*Working women who are not married above the ideal age in Indonesia have their own anxiety due to often getting stigma from society as old virgins, not selling well, choosing a lot and others. This paper will try to analyze the anxiety of working women with sociological analysis using feminism theory, the research method using descriptive qualitative methods with purposive sampling of informants selection on six working women with an age range of 30-35 years with a minimum education of S1. The results of the study show that working women who are nervous about the age of marriage come from the encouragement of the family and social environment, besides that the cultural view of the ideal marriageable age in society makes unmarried women above the ideal age as a failure.Keywords: Feminism Theory, Age of Marriage Anxiety, Working Women.